2021
DOI: 10.1111/ene.15081
|View full text |Cite
|
Sign up to set email alerts
|

Baseline characteristics and effects of fingolimod on cognitive performance in patients with relapsing‐remitting multiple sclerosis

Abstract: Background and purpose: Studies reporting the baseline determinants of cognitive performance and treatment effect on cognition in patients with multiple sclerosis (MS) are limited. We investigated the baseline correlates of cognition and the long-term treatment effects of fingolimod 0.5 mg once daily on cognitive processing speed and attention in patients with relapsing-remitting MS. Methods:This post hoc analysis pooled data from the phase 3 FREEDOMS and FREEDOMS II trials (N = 1556). We assessed the correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Nevertheless, EDSS was associated with cognitive impairment in the patients with RRMS who were on fingolimod therapy. Similarly, a clear relationship has been reported between EDSS and PASAT-3 score in the phase 3 FREEDOMS and FREEDOMS II trials (Langdon et al, 2021).…”
Section: Fingolimod Mechanism Of Action Involves Reduction In Autoag-supporting
confidence: 61%
See 3 more Smart Citations
“…Nevertheless, EDSS was associated with cognitive impairment in the patients with RRMS who were on fingolimod therapy. Similarly, a clear relationship has been reported between EDSS and PASAT-3 score in the phase 3 FREEDOMS and FREEDOMS II trials (Langdon et al, 2021).…”
Section: Fingolimod Mechanism Of Action Involves Reduction In Autoag-supporting
confidence: 61%
“…Fingolimod treatment has been shown to improve cognitive performance, which may be due to the fact that it crosses the blood–brain barrier, encouraging myelin preservation, repair, and neurological function normalization (Groves et al, 2013). Phase 3 FREEDOMS and FREEDOMS II trials determined cognitive performance in patients with MS using the 3‐second Paced Auditory Serial Addition Test (PASAT‐3) and have suggested that early fingolimod therapy may provide long‐term cognitive improvement (Langdon et al, 2021). In a randomized controlled trial (the GOLDEN study), the benefits of fingolimod therapy on cognitive functions have been verified using Rao's Brief Repeatable Battery and Delis–Kaplan Executive Function System test (Comi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DMTs may affect cognition by reducing the progression of brain atrophy and relapse rates. 37 , 38 Emerging research described early treatment with fingolimod as providing a cognitive advantage in those with RMS by allowing adaptive neuroplastic changes and providing anti-inflammation effects 38 while Mattioli et al 37 reported that natalizumab-aided executive functioning and memory improvements through preservation of parahippocampal and frontal grey matter. However, there remains insufficient evidence of the efficacy of DMTs in the treatment of cognitive impairments in pwMS and no medication has been approved, specifically for these symptoms.…”
Section: Discussionmentioning
confidence: 99%